Collaborative Decision Making for Complex Product and Process Development: A Study of Process and Software for Decision Making - Rajendran, Nanthagopal (2011)
The development of product and process is the core activity for the firms to be competitive in the global market. Today the firms are in a position to improve their product and process development continuously in order to sustain among their competitors. A lot of efforts have been made from the mid of 20th century in this process with the help of new technology, method and attitude. The course of product and process development is purely a knowledge based activity which has to be supported by several personnel in a firm. Hence the decision making process should be collaborative during the period of product or process development in order to make the process effective. This study aims to review the different approaches available for the collaborative decision making for complex product and process development. In line with that, first the concept of collaborative decision making and the different approaches of collaborative decision making have to be understood. Then to support the collaborative decision making throughout the product development, the different available software in terms of scope and functionality have to be studied. In order to understand the collaborative decision making in real time business environment, relevant case studies should be analysed. In order to understand the concept of Collaborative Decision Making and to execute the same in an organisational environment, systematic approaches should be followed for implementation. In this study the concept of Collaborative Decision Making in the complex product and process development has been discussed with the support of different approaches like Concurrent Engineering, Programme Management and Product Lifecycle Management. To support and implement the collaborative Decision making approaches in an organisation, software plays a vital role to connect the different users located across geographically. Therefore this study aims at focussing on analysing the software available in the market for decision making with various aspects.